TAHOKOMB in complex of the surgical treatment patients with supratentorial brain tumors - Glavatskij, A.; Lysenko, S.; Kulik, A.; Danchuk, S. (Ukrainian Neurosurgical Journal, 2006)
The article is dedicated to improvement result surgical treatment patients with supratentorial brain tumors. The optimization of such treatment is realized on base of the preventive maintenance haemoragical and liquor-circulation complications, as the most significant factor of the deterioration of the condition patient at early postoperative period. The organized analysis 40 patients with supratentorial brain tumors with different hystostructure. The organized analysis of the reason of the development of haemoragical and liquor-circulation complications when removing the supratentorial tumors. The worked out methods intraoperation preventive maintenances complication data by means of material TAHOKOMB (the production "Nykomed" Austria). Motivated need of the use modern haemostatic facilities, as preparation to first line in complex of the surgical treatment patients this supratentorial brain tumors. The typical clinical event is brought.